INVESTIGATION OF CYTOKINE SYNTHESIS AT THE LEVEL OF INDIVIDUAL CELLS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The idea of localisation of antigens in tissues using antibodies was first implemented in the early 40s years. Subsequently, immunocytochemical methods became widely used in molecular clinical diagnostics, and since the mid-70s, after the discovery of monoclonal antibodies, their role has increased even more.